CD33M inhibits microglial phagocytosis, migration and proliferation, but the Alzheimer's disease‐protective variant CD33m stimulates phagocytosis and proliferation, and inhibits adhesion. Issue 2 (5th April 2021) - Butler, Claire Ann; Thornton, Peter; Brown, Guy Charles
Abstract: CD33 is a Siglec (sialic acid‐binding immunoglobulin‐type lectin) receptor on microglia. Human CD33 can be alternatively spliced into two isoforms: the long isoform (CD33M) and a shorter isoform (CD33m) that lacks the sialic acid‐binding site. CD33m appears to protect against Alzheimer's disease; however, it remains unclear how. To investigate potential mechanisms by which CD33m may confer protection, we expressed the CD33m and CD33M isoforms of human CD33 in mouse BV‐2 and human CHME3 microglial cells and assessed microglia functions. In the BV‐2 cells, CD33M inhibited microglial phagocytosis of beads, synapses, debris and dead cells, while CD33m increased phagocytosis of beads, debris and cells. RNAi knockdown of the endogenous mouse CD33 increased phagocytosis and prevented CD33m's (but not CD33M's) effect on phagocytosis. CD33M increased cell attachment but inhibited cell proliferation, while CD33m did the opposite. We also found that CD33M inhibited cell migration. In human CHME3 cells, CD33M increased cell attachment, but inhibited phagocytosis, proliferation and migration, whereas CD33m did the opposite. We conclude that CD33M inhibits microglial phagocytosis, inhibits migration and increases adhesion, while CD33m increases phagocytosis, proliferation and inhibits adhesion. Thus, CD33m might protect against Alzheimer's disease by increasing microglial proliferation, movement and phagocytosis of debris and dead cells. Abstract : Over‐expression of Alzheimer's risk variant of CD33, CD33M, inhibits phagocytosis, proliferation and migration but increases adhesion to fibronectin in microglia. While over‐expression of Alzheimer's protective variant of CD33, CD33m, does the opposite. We suggest that CD33m has a modest gain of function and may be protective in Alzheimer's disease by increasing overall microglia activation, promoting efficient removal of neuronal debris and amyloid beta.